Proses Terapi Sensori Integrasi Pada Anak Autis Dalam Meningkatkan Interaksi Sosial Di Pusat Terapi Autis Yasmin - Maharra Ulfa Kristamara; Ati Kusmawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Sensory Integration Therapy is an approach that focuses on sensory stimulation to improve sensory processing and adaptive responses in individuals with sensory disorders, one of which is children with autism. Sensory integration therapy makes it easier for autistic children to communicate to be better understood and to create good social interactions. Therefore, the Yasmin Autism Therapy Center carries out Sensory Integration Therapy to improve social interaction in autistic children. This research aims to determine the application of sensory integration therapy at the Yasmin Autism Therapy Center to improve social interaction in autistic children and determine the obstacles in implementing sensory integration therapy. Data collection techniques include documentation, observation and interviews. The results of the research show that the stages of Sensory Integration Therapy at the Yasmin Autism Therapy Center are providing simple instructions, a series of sequential activities and honing concentration, consistency and endurance in activities through play. Supporting factors for sensory therapy activities include good collaboration between therapists and parents. Meanwhile, the obstacles to children's communication are difficult factors, limited therapy tools, and limited therapy time.